1853. Impact of Antimicrobial Stewardship Interventions on Antimicrobial Utilization in Asymptomatic Bacteriuria. (26th November 2018) - Shah, Punit; Ike, Chiamaka; Thibeaux, Meghan; Rodriguez, Emilyn; Maddox, Shermel; Daoura, Nicolas
Abstract: Background: Antimicrobial therapy for asymptomatic bacteriuria (ASB) is often unnecessary and is a common reason for inappropriate antimicrobial use in hospitalized patients. ASB treatment leads to development of resistance, drug toxicities and increased risk of Clostridium difficile infections. We evaluated a multi-faceted interdisciplinary antimicrobial stewardship approach to reduce unnecessary antimicrobial utilization for ASB. Methods: This was an IRB approved study evaluating the impact of antimicrobial stewardship on antibiotic utilization for ASB in a pilot medical-surgical unit. The pre-intervention phase was from August to October 2017 and the post-intervention phase was from December to March 2018. The intervention phase consisted of educational in-services to hospitalist groups, Infectious Diseases physicians, nurses, and pharmacists. An electronic real-time surveillance system was used to identify positive urine cultures. The clinical pharmacist for the pilot unit classified the patient as either ASB or urinary tract infection, and made stewardship interventions to stop unnecessary antimicrobial therapy for ASB. Results: There were 65 and 77 patients with bacteriuria in the pre- and post-intervention phases. Among these, ASB was present in 29 (45%) and 27 (35%) patients, respectively. After excluding those receiving antibiotics for concurrent non-urinary indications, education alone decreased ASB treatment from 18 (62%) to 12 (44%) patients in the pre- and post-intervention phases respectively [RR 0.72, 95% CI 0.42–1.17, P = 0.19]. Pharmacist interventions in combination with education further decreased unnecessary ASB treatment from 18 (62%) to 6 (22%) patients [RR 0.36, 95% CI 0.16–0.72, P = 0.003]. Conclusion: Education to healthcare professionals alone did not significantly decrease unnecessary ASB treatment. However, in combination with real-time pharmacist interventions there was a significant decrease in antimicrobial therapy for ASB. With increasing antimicrobial resistance, healthcare institutions should evaluate the role of interdisciplinary antimicrobial stewardship interventions to reduce unnecessary antimicrobial utilization for ASB. Disclosures: All authors: No reported disclosures.